Aneurysm - Murai, Yasuo (IntechOpen, 2012)
This book's focus is on diagnosis and treatment of intracranial aneurysm, abdominal and thoracic aortic aneurysms. It addresses neurosurgical, vascular and cardiothoracic surgeons and interventional radiologists, but also anyone engaged in vascular medicine. It presents is an effort to collect an up-to-date account of existing knowledge, involving recent developments in this field. Various experts described details of established knowledge or newly recognized advances associated with diagnosis, treatment, perioperative management and mechanism. This is the first book that deals with the whole body aneurysm, such as cerebral aneurysm, abdominal aneurysm, and splenial aneurysm and to learn the latest developments in other fields is always useful. I hope this book will be used worldwide by vascular surgeons and interventionalists enhancing their knowledge and stimulating the advancement of this field.